2006
DOI: 10.2298/hel0645055d
|View full text |Cite
|
Sign up to set email alerts
|

Expressivity of tocopherol mutations in sunflower

Abstract: Influences of genetic background, ontogenesis and environment on tocopherol mutations in sunflower were estimated in this study. The content of α/β-tocopherols varied from 40/60 to 60/40% in seeds of different inbred lines containing the tph1 gene. The lines containing the tph2 gene ranged widely in α/γ-tocopherols, from 0/100 to 80/20%. A double mutation showed variability in different inbred lines in α/β/γ/δ-tocopherol contents from maximum expressivity of 0/0/60/40 to minimum 40/25/25/10%, due to incomplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…However, leaves contained either similar amounts of both gamma‐ and delta‐tocopherol (TS‐1) or predominantly gamma‐tocopherol (IAST‐4), which is explained on the basis of low expressivity of the tph1 mutation in leaves. This was described by Demurin et al 15 and also observed in the mutants with increased levels of beta‐tocopherol studied in the present research.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, leaves contained either similar amounts of both gamma‐ and delta‐tocopherol (TS‐1) or predominantly gamma‐tocopherol (IAST‐4), which is explained on the basis of low expressivity of the tph1 mutation in leaves. This was described by Demurin et al 15 and also observed in the mutants with increased levels of beta‐tocopherol studied in the present research.…”
Section: Discussionsupporting
confidence: 90%
“…However, beta‐tocopherol levels in leaves were about three times lower than those found in seeds, suggesting a lower expression of the tph1 mutation in leaves. Demurin et al 15 described no expressivity of tph1 mutation in sunflower leaves in analyses conducted using thin layer chromatography. Since the beta‐tocopherol mutant LG‐15 analysed by Demurin et al 15 is allelic to T589,30 differences in beta‐tocopherol expression in leaves between the two studies might result from the more sensitive analytical technique used in the present research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced growth in plants less tolerant to herbicides, after herbicide treatment, is considered to be a consequence of poor root growth and consequently decreased nutrient uptake (Soltani et al 2008). When testing herbicide tolerance one must consider that both environmental factors and the genetic basis of the genotypes receiving the resistance genes have large influence on the expression of herbicide resistance (Jocić et al 2011), especially bearing in mind that genetic background was found to influence the expressivities of some mutations in sunflower (Demurin et al 2006). Considering a wide range in plant growth response to stress conditions in sunflower in respect to different genetic background (Pereyra-Irujo et al 2008, Ahmad et al 2009), we tested several genotypes in order to identify universal treatment for detection of TBM resistance.…”
Section: Hofmentioning
confidence: 99%